Talent Management, HR Planning and Career Development on Employee Performance of PT Pelindo Terminal Petikemas Surabaya - Taufik, Moch; Sumartik, Sumartik; Abadiyah, Rifdah (Jurnal Ilmu Manajemen Advantage, 2024)
In this study, the researcher chose PT. Pelindo Container Terminal Surabaya as a research object with the status of Organic (Permanent) employees. The purpose of the study is to determine the influence of talent management, HR planning and career development on employee performance at PT. Pelindo Surabaya Container Terminal. This type of research is quantitative which includes primary and secondary data. Sampling technique, Non Probability Sampling technique, the total population is 222 employees with Organic (Permanent) status. The method used in Non Probability Sampling is Purposive Sampling. The sampling technique used the sloving technique totaling 69 respondents as a sample. The method of collecting data disseminated questionnaires directly to respondents and direct observation of the research object. The data collection technique of this study uses an answer interval scale measured using a Likert scale of 1-5. The data analysis technique uses an outer and inner model and data testing uses Smart Partial Squer (PLS). The results of the study show that Talent Management has a positive and insignificant effect on employee performance. HR planning has a positive and significant effect on employee performance. And career development has a positive and insignificant influence on employee performance. The findings of the study show that the company provides a job promotion for each individual employee who is selected, this is less effective for employees who are not selected so that they have insignificant results.